Shell Shapes Framed in Steel - Geiger, David H. (Engineering Journal, 1965)
In considering the use of steel framing for shell shapes, ones attention turns immediately to the problems of detailing members and designing joints. The author had occasion to consider these problems while doing the structural design for the Johnson Wax Pavilion at the New York Worlds Fair. An architectural feature of this pavilion consists of six "petals" or shell shapes which flare out from the top of columns that also support the theatre. It was decided to frame these petals in steel. The framing for one petal consists of a "spine" which is in effect a continuation of the column, curved "ribs" transverse to this spine, and two warped channels and a warped angle which serve as edge beams. In addition to doing the structural design, the author also supplied the fabricator with the geometry required for detailing these members. From this data individual pieceswere detailed and shop drawings made.